MERRILL: micromagnetic earth related robust interpreted language laboratory - Ó,Conbhuí P; Williams,W; Fabian,K; Muxworthy,AR; Ridley,P; Nagy,L (Geochemistry, Geophysics, Geosystems, 2018)
Complex magnetic domain structures and the energy barriers between them are responsiblefor pseudo-single-domain phenomena in rock magnetism and contribute significantly to the magneticremanence of paleomagnetic samples. This article introduces MERRILL, an open source software packagefor three-dimensional micromagnetics optimized and designed for the calculation of such complexstructures. MERRILL has a simple scripting user interface that requires little computational knowledge to usebut provides research strength algorithms to model complex, inhomogeneous domain structures inmagnetic materials. It uses a finite element/boundary element numerical method, optimally suited forcalculating magnetization structures of local energy minima (LEM) in irregular grain geometries that are ofinterest to the rock and paleomagnetic community. MERRILL is able to simulate the magnetic characteristicsof LEM states in both single grains, and small assemblies of interacting grains, including saddle-point pathsbetween nearby LEMs. Here the numerical model is briefly described, and an overview of the scriptinglanguage and available commands is provided. The open source nature of the code encourages futuredevelopment of the model by the scientific community.